Correlational-regression analysis application for the forecast of the specialists with higher education requirement in Russian economy - Potekhina, Nina; Shulinina, Yulia; Kuzmina, Natalia; Potalisina, Ludmila; Sannikova, Inessa (International Journal of Economics and Financial Issues, 2016)
The present study was intended to investigate a hypothesis about the impact of the following parameters: dynamics of gross domestic product, dynamics of fixed assets, dynamics of labour productivity, dynamics of the level of remuneration and dynamics of fixed asset investments on the number of employees with higher education in Russia. The correlational-regression analysis confirmed the influence of dynamics of fixed assets on the number of employees with higher education. Also authors have generated the forecast about future demand for specialists with higher education and dynamics of fixed assets for the period from 2015 to 2025 years.